Tuberculosis and COVID-19 in Children and Adolescents. Two Waves of the Pandemic: Experiences and Conclusions - E. S. Ovsyankina; L. V. Panova; M. F. Gubkina; A. E. Ergeshov; I. Yu. Petrakova; E. A. Krushinskaya (Туберкулез и болезни лёгких)
The objective of the study: to investigate diagnostics, course and outcomes of COVID-19 in children and adolescents with tuberculosis in relation to the epidemic control activities.Subjects and Methods: during the pandemic of coronavirus infection (the first and second waves), 83 patients aged 2 to 17 years (41 children and 42 adolescents) were followed up. 62 (74.7%) children got infected with the novel coronavirus infection among 82 patients treated at the clinic over this time.Results. COVID-19 has been found to be highly contagious in the group of children staying in the ward, employees working with children and adolescents were the source of infection. Compliance with sanitary and infection control activities allows reducing the likelihood of the viral infection spread in the group of children and adolescents. The respiratory syndrome is not a major sign for the diagnosis of COVID-19 in children and adolescents with respiratory tuberculosis. For the diagnosis of COVID-19, targeted immunological and microbiological tests are important. Most patients with clinical manifestations of the coronavirus infection (79.4% of cases) were diagnosed with a mild course of the disease. Co-infection (tuberculosis and COVID-19) caused no mutual aggravation. No adjustment of chemotherapy was required, and the duration of treatment didn’t increase including short-course chemotherapy regimens with multiple/extensive drug resistant Mycobacterium tuberculosis and in patients after surgery.